A rare case of mixed connective tissue disease presenting with central nervous system glioma, vasculitis and polymyositis - Parikh, Rushabh; Ingale, Pushkar; Dave, Dhaval; Pendse, Manish; Patil, Smita; Bhate, Archana (International Journal of Research in Medical Sciences, 2017)
Mixed connective tissue disease (MCTD) was first recognized by Sharp and Colleagues in 1972 among a group of patients with overlapping clinical features of systemic lupus erythematosis (SLE), scleroderma and myositis, with the presence of distinctive antibodies against, what now is known to be U1-ribonucleoprotein (RNP). We report an unusual case of a 23-year old female with MCTD characterized by the coexistence of signs, symptoms and immunological features of 3 defined autoimmune diseases SLE, systemic sclerosis (SSc), polymyositis (PM) and an unusual presence of central nervous system (CNS) Glioma.